Clinical researchVideolaryngoscopic and videostroboscopic evaluation following laser CO2 and conventional cordectomy of Tis and T1 glottic carcinoma - Lachowska, Magdalena; Osuch-Wójcikiewicz, Ewa; Bruzgielewicz, Antoni (Archives of Medical Science, 2010)
Introduction: This paper is an analysis of long-term functional results, observed on videolaryngoscopic and videostroboscopic examination, of two different types of surgical intervention for Tis and T1 glottic carcinoma: laryngofissure conventional cordectomy and endoscopic laser CO2 cordectomy, with or without additional radiation therapy (using 60Co). Material and methods: A total of 46 patients with Tis and T1 glottic carcinoma, 43 men (93.48%) and 3 women (6.52%), served as subjects. All were treated surgically with laryngofissure conventional cordectomy (15 patients, 32.61%) or endoscopic laser CO2 cordectomy (31 patients, 67.39%). The procedures were performed in the Department of Otolaryngology at the Medical University of Warsaw between November 1990 and February 2004. Videolaryngoscopic and videostroboscopic examinations were conducted a minimum of 3 years after the surgery, between January 2006 and February 2007. The appearance of the neocord (the scar after cordectomy), scar or synechia formation in the anterior commissure, movements of the vocal folds on respiration and phonation, difference in level between the neocord and the normal vocal fold, glottic closure, phonation type, and ventricular folds hyperfunction were examined. The symmetry of vocal fold vibrations, regularity of vibrations, glottic closure, amplitude of vibrations, and mucosal wave were also evaluated. Results: In our study, the videolaryngoscopic and videolaryngostroboscopic examination showed a significantly higher occurrence of the following findings in patients after endoscopic laser cordectomy: phonation at the glottic level, complete glottic closure, and a tendency to vibration of the neocord on phonation. Conclusions: Ventricular hyperfunction on phonation and scar or synechia formation in the anterior commissure were observed statistically more frequently in patients after laryngofissure conventional cordectomy.